Effect of workplace bullying on psychological strain and job performance: organisational support as moderator - Hassan, Arif; Sadiq Al Bir, Ahmad Talib (2014)
Workplace bullying is an anti-social behaviour which is defined as continuous harassment or “mobbing” of individual employee experienced for a relatively longer period of time. This may take several forms such as constant abuse, offensive remarks or teasing, ridicule, social exclusion, harassment, physical violence etc. The situation may be damaging to the wellbeing and job performance of the employee. However, if the organisation provided necessary support to the employee the effect of bullying could be mitigated. The paper examines these issues in selected Malaysian organisations. A randomly selected sample of 231 employees representing different industry, size, gender, age, experience and job position responded to a self-rated questionnaire which measured the study variables, namely workplace bullying, psychological strain, self-rated job performance, and organisational support. The result indicated a significant effect of bullying on psychological strain and job performance. No significant moderation effects of perceived organisational support were found in the relationship between workplace bullying and pychological strain as well as job performance. However, bullying demonstrated full moderation effect between organisational support and self-rated job performance. The findings are discussed in the light of existing literature.